Gaining comprehensive biological insight into the transcriptome by performing a broad-spectrum RNA-seq analysis - Sayed Mohammad Ebrahim Sahraeian (Nature Portfolio, 2017)
RNA-seq is widely used for transcriptome analysis. Here, the authors analyse a wide spectrum of RNA-seq workflows and present a comprehensive analysis protocol named RNACocktail as well as a computational pipeline leveraging the widely used tools for accurate RNA-seq analysis.